The reliability and validity of Turkish version of dsm-5 level 2 substance use disorder scale - Yalın Sapmaz, Şermin; Sargın, Enis; Ergin, Canem; Özek Erkuran, Handan; Öztürk, Masum; Aydemir, Ömer (Journal of Dependence, 2016)
Objective: In this study, it was aimed to assess the validity and reliability of Turkish version of DSM-5 Level 2 Substance Use Disorder Scale.Methods: Study groups consisted of a clinical sample diagnosed with substance use disorder being treated in a child psychiatry unit and a community sample. A total number of 92 parents and 128 adolescents were included in the study. Clinical sample consisted of 34 adolescents between 11-17 years old that were diagnosed with substance use disorder according to DSM-5 diagnostic criteria and being followed up in Celal Bayar University Medical School Child Psychiatry Unit and Alcohol and Substance Treatment Unit for Children and Adolescents of Tepecik Research and Training Hospital and 33 parents. Addiction Profile Index for Adolescents (BAPI) form was used alongwith DSM-5 Level 2 Substance Use Disorder Scale for assessment. For reliability analyses, internal consistency coefficient and item-total score correlation analysis were carried out; concurrent validity was measured for validity analyses as well as developing ROC curve to identify discriminative quality of the scale regarding clinical and community samples.Results: Cronbach alpha internal consistency coefficient was found as 0.847 and 0.760 for child and parent forms, respectively. Regarding concurrent validity, correlation of the scale’s child form with BAPI- Adolescent form was 0.742. Area under the ROC curve as a result of ROC analysis yielded a measure of 0.964 for child form and 0.990 for parent form.Conclusion: Results indicate that DSM-5 Level 2 Substance Use Disorder Scale- Turkish Version could be utilized as a valid and reliable instrument for both clinical and research purposes.
Keywords: DSM-5 Level 2 Substance Use Disorder Scale; reliability; validity